Synthesis and Mesomorphic Properties of 4-(Methylthio)benzylidene-4’-n-alkanoyloxyanilines - Ha, Sie-Tiong; Lee, Teck-Leong; Yeap, Guan-Yeow; Lin, Hong-Cheu; M. Ito, Masato; T. Subramaniam, Ramesh (Asian Journal of Chemistry, 2011)
A homologous series of Schiff base esters, 4-(methylthio)benzylidene-4'-n-alkanoyloxyanilines possessing even number of carbon atoms at the alkanoyloxy chain (Cn-1H2n-1COO-, n = 2 to 18) was synthesized. The structure of the 4-(methylthio)benzylidene-4'-n-alkanoyloxyanilines was confirmed by elemental analysis and spectroscopic techniques including FT-IR, 1H and 13C NMR and EI-MS. Mesomorphic properties were evaluated by differential scanning calorimetry and polarizing optical microscopy techniques. Whilst n-butanoyloxy to n-octanoyloxy derivatives exhibited monotropic nematic phase, n-ethanoyloxy and n-decanoyloxy to n-octadecanoyloxy derivatives were non-mesogenic compounds. The mesomorphic properties of the present series were compared with other structurally related series to establish the chemical structure-mesomorphic property relationship.